Restructuring the geography of domestic tourism in South Africa - Rogerson, Christian M. (Bulletin of Geography. Socio-economic Series, 2015)
Domestic tourism is relatively under-represented in tourism scholarship. This article attempts to analyse the role of domestic tourism in one of the 'emerging world regions' of tourism. In the case of South Africa domestic tourism represents a significant element of the country's tourism economy. The objectives are to provide (i) an analysis of the growth, contemporary spatial patterns and restructuring of domestic tourism in South Africa; and (ii) an assessment of emerging policy debates issues taking place about domestic tourism. Using a detailed local level data base on tourism flows this paper provides fresh insight into the character and changing geography of domestic tourism in South Africa. The nature and dynamics of domestic tourism are shown to have shifted since democratic transition. The restructured geography of domestic tourism exhibits a number of continuities and changes with earlier times. Government is seeking to use domestic tourism as a basis for addressing spatial unevenness in patterns of tourism development. In terms of recent spatial change it is revealed the most significant developments are the strengthening of Ethekwini as the country's leading domestic tourism destination and the relative demise of Cape Town as a hub for domestic tourists.